2022
DOI: 10.1186/s40359-022-00864-y
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural measurement invariance of the Quality of Life Enjoyment and Satisfaction Questionnaire-Short form across ten countries: the application of Bayesian approximate measurement invariance

Abstract: Background The Quality of Life Enjoyment and Satisfaction Questionnaire-Short Form (Q-LES-Q-SF) is the most frequently used generic quality of life (QOL) measure in many countries and cultures worldwide. However, no single study has been carried out to investigate whether this questionnaire performs similarly across diverse cultures/countries. Accordingly, this study aimed to assess the cross-cultural measurement invariance of the Q-LES-Q-SF across ten different countries. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The reporting of demographics such as race/ethnicity, highest level of parental education, and socioeconomic status were limited, and when reported were not specifically considered in demonstration of ME. We acknowledge that diversity certainly plays a role in access and should be considered when a PROM is undergoing cross-cultural adaptation (51,52) but should not affect determination of ME when a pen-paper PROM is adapted to e-version. Furthermore, only half of the studies included evaluated disease-specific PROMs for children and only 1 study evaluated a disease-specific PROM utilized by pediatric gastroenterologists despite increasing evidence that their use in clinical care can help focus goals and therapeutic decisions and produce better health outcomes (11,53,54).…”
Section: Discussionmentioning
confidence: 99%
“…The reporting of demographics such as race/ethnicity, highest level of parental education, and socioeconomic status were limited, and when reported were not specifically considered in demonstration of ME. We acknowledge that diversity certainly plays a role in access and should be considered when a PROM is undergoing cross-cultural adaptation (51,52) but should not affect determination of ME when a pen-paper PROM is adapted to e-version. Furthermore, only half of the studies included evaluated disease-specific PROMs for children and only 1 study evaluated a disease-specific PROM utilized by pediatric gastroenterologists despite increasing evidence that their use in clinical care can help focus goals and therapeutic decisions and produce better health outcomes (11,53,54).…”
Section: Discussionmentioning
confidence: 99%
“…It was uncertain whether these same six life domains would collectively provide a valid QOL measure in a Japanese context, given the cultural differences. Generally, the construct of QOL appears to be quite similar in different cultures, but it has also been reported that different cultures respond differently to specific items related to QOL 16,17 . It remains unclear whether subjective QOL is equally reliable and valid in Japanese culture, given that it is influenced by individual life perspectives, religion, ethnic customs, and values.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the construct of QOL appears to be quite similar in different cultures, but it has also been reported that different cultures respond differently to specific items related to QOL. 16 , 17 It remains unclear whether subjective QOL is equally reliable and valid in Japanese culture, given that it is influenced by individual life perspectives, religion, ethnic customs, and values. Hence, this study developed the Japanese version of the BBQ (BBQ‐J) and examined its reliability and validity.…”
Section: Introductionmentioning
confidence: 99%